Comparative Analysis of Double and Trifocal IOL Implantation in Femtosecond Laser-Assisted Cataract Surgery - O. I. Orenburkina (Oftalʹmologiâ, 2019)
Purpose: to compare the clinical results of implantations of bi-and trifocal intraocular lenses (IOL) in femtosecond laser-assisted cataract surgery. Patients and methods. The article presents the results of the Acrysof IQ Panoptix trifocal lens implantations in 84 patients (112 eyes) — the main group and Acrysof IQ Restor bifocal IOL implantations in 52 patients (98 eyes) — the control group. All patients underwent femtosecond laser-assisted cataract surgery (FLACS). The following data were evaluated: uncorrected distance visual acuity (UCDVA) , uncorrected near visual acuity (30–45 cm) and at an average distance (50–70 cm) at discharge, after 14 days, 1 and 3 months after the surgery under photopic and mesopic lighting conditions. Postoperative refractometry data; the defocusing curve was performed in patients with a high UCDVA (0.9–1.0) monocularly under photopic conditions using standard optotypes 14 days after surgery; aberrometry indicators. Results. It was shown that both lenses provided high uncorrected distance and near visual acuity in photopic lighting conditions. At the same time, the Acrysof IQ Panoptix lens provided significantly better visual acuity at an intermediate distance and was more resistant to defocusing conditions. Refraction data: after 1 month, emmetropia was observed in 87 % of patients in the main group and in 85 % of control group, after 6 months — 92 and 89 % respectively. There were no significant differences in high order aberrations and total aberrations between patients of the compared groups. Conclusion. The use of the PanOptix trifocal lens made it possible to obtain maximum visual acuity at different distances, regardless of the level of illumination.